Synthesis and antihyperlipidaemic activity of a new piperine derivative - Damdindorj, Mungunnaran; Borjihan, Gereltu; Gendaram, Odontuya; Bold, Bayarmaa (Mongolian Journal of Chemistry, 2021)
Long pepper (Piper longum Linn.) is widely used as a medicinal substance in traditional Ayurvedic medicine. Its major alkaloid piperine is the main active constituent with various therapeutic activities and has low solubility in water. In this study, a soluble new derivative of a piperine alkaloid, named N-leucinylpiperamide was synthesized. The animal experiment showed that N-leucinylpiperamide has more hypolipidemic effects than commercially available simvastatin and piperine in modulating serum lipids in Wistar male rats. At the amount of 10 mg/kg bw, it significantly reduced TC (-52.4%), TG (-61.7%), and LDL-C (-27.8%), respectively, and increased HDL-C (+147.4%) in the serum of the high-lipid model group. Furthermore, the synthesized N-leucinylpiperamide had no noticeable cytotoxicity against HepG2 cell line in vitro. Thus, our study shows that N-leucinylpiperamide has an ability to improve serum lipid profile in hyperlipidemic model rats and could be a valuable promising agent for the preventing hyperlipidemia.